Innovative Protective Solutions for Manhole Cleaners in Pakistan: Material Analysis, Safety Gear Development, and Antimicrobial Advancements - Zoha Qadeer , Fariha Saeed , Mona Gulzar , Aiman Amjad , Anum Shamshad (Cuestiones de Fisioterapia, 2025)
Workers who clean manholes in Pakistan encounter serious health hazards due to dangerous working environments, including exposure to poisonous gases, harmful pathogens, and chemicals present in sewage systems. A REACH documentary revealed that health-related issues linked to their occupation lead to 80% of manhole workers dying before they reach the age of 60.